HORIZONTAL CSR AND GOTONG ROYONG COMMUNICATION - Wijaya, Bambang Sukma (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2012)
In an era of increasingly horizontal, equal, and communal communication, new models are needed to develop corporate social responsibility (CSR) programs that are more effective and relevant. Indonesia has a rich culture that can contribute to the development of new models of corporate communication, one of which is Gotong Royong communication. This article elaborates on horizontal models of CSR and their relationship to the culture of Gotong Royong in Indonesia. Horizontal CSR carries 3Cs: Community, Collaboration, and Cooperation. This study inspires companies and professional organizations to explore new forms of CSR programs based on social capital, social relations, and local wisdom that are equal and less selfish. To cite this article:Wijaya, B. S. (2012). Horizontal CSR and Gotong Royong Communication. Journal Communication Spectrum, 2(1), 43-62.